AN ANALYSIS OF JARGONS USED BY RECEPTIONISTS IN FRONT OFFICE HOTELS AT LOMBOK - Siti Lathifah (International Journal of Social Science, 2023)
This study aimed at identifying and describing the linguistic forms, the meanings and the functions of jargon used by receptionists of the front office department at Lombok Hotel. This study was conducted in qualitative method. The front office jargons were investigated in spoken and written forms. The subjects of this study were receptionists of the front office department at Lombok. The methods of data collection were observation, documentation and interview. This study found jargon were used by receptionists in front office department. It was found that the jargon was in the form of noun phrases abbreviation, noun, clipping, affixation, borowing , acronym , preposition phrases , verb , adjective , and coinage . The meanings of jargon were identified by investigating technical meaning. Besides, this study found that there were two functions of the jargon, (1) providing a technical or specialist language to make communication more efficient and (2) encouraging group solidarity. This study concluded that jargon is a way toexpress the feeling of the community and also have their own specific language